Evaluation of the Learning Curve and Complications Related to Hand-Assisted Laparoscopic Appendectomy in Children with Acute Appendicitis - Hoseinpour, Mehrdad; Nazem, Masoud; Khaledifar, Borzoo (Iranian Journal of Pediatric Surgery, 2017)
Introduction: Previous studies have shown that according to the learning curve, one’s knowledge and skills increase with experience and repetition. However, no studies have yet proved that the learning curve can be generalized to medical procedures. Therefore, this study aimed to evaluate the learning curve and complications of hand assisted laparoscopic appendectomy (HALA) in children with acute appendicitis. Materials and Methods: In a prospective randomized study in 2016, ninety patients aged 8-16 years were selected for appendectomy. The participants were then consecutively divided into three groups according to admission time. The first, second, and third groups were operated on by an attending pediatric surgeon, an attending pediatric surgeon and a pediatric surgical fellow (a surgeon who is studying the subspecialty of pediatric surgery) and in the third group only a pediatric surgical fellow, respectively. For each surgery, duration of surgery and hospitalization was determined and recorded, and the time trend of surgery was determined and compared in all three groups using the learning curve. Results: The mean duration of surgery of the groups operated on by an attending, an attending and a fellow, and a fellow alone was 38.7±12.8, 46.9±8.8 and 48.5±11.3 respectively, with a significant difference among the three groups (p=0.002). During the surgery, duration of surgery in the fellow and attending group and the fellow group decreased over time. Conclusion: The learning curve can be generalized to medical procedures and experiences. Duration of appendectomy for fellows can decrease over time as they become more skilled. Usually after performing 30 surgeries and gaining experience, fellows will be able to perform appendectomy nearly as fast as attending surgeons. In the meantime, the root causes of the fluctuations observed during surgery should be scientifically examined and resolved.